The Effect of the Card Sort Type Active Learning Method on the Indonesian Language Learning Outcomes of Fourth-Grade Elementary School Students - Rukayah; Sitti Rahmi; A.Risma Wati (Journal of Primary Education Innovation and Research, 2026)
This study is a quantitative pre-experimental study that aims to determine the effect of the Card Sort Type Active Learning Method on the Indonesian language learning outcomes of fourth-grade students at SD Inpres 12/79 Arasoe, Cina District, Bone Regency. This study employed a One-Group Pretest–Post-test design. The population in this study consisted of 22 fourthgrade students at SD Inpres 12/79 Arasoe, with the sampling technique using saturated sampling. The data collection technique used was a test to determine students’ learning outcomes before and after the implementation of the Card Sort Type Active Learning Method through three treatments. The data analysis techniques used were descriptive analysis and inferential statistical analysis using the Paired Sample t-Test. The results of the study before the implementation of the Card Sort Type Active Learning Method showed that the students’ pretest scores were in the very poor category, with an average score of 37.59. After the implementation of the Card Sort Type Active Learning Method, the students’ posttest results changed to the excellent category, with an average score of 78.86. The results of the statistical analysis indicated a significant difference in students’ learning outcomes before and after using the Card Sort Type Active Learning Method. The study concludes that the Card Sort Type Active Learning Method has a significant effect on the Indonesian language learning outcomes of fourth-grade students at SD Inpres 12/79 Arasoe, Cina District, Bone Regency.